A Novel CLCN5 Splice Site Mutation in a Boy with Incomplete Phenotype of Dent Disease - Bitsori, Maria; Vergadi, Eleni; Galanakis, Emmanouil (Journal of Pediatric Genetics, 2019)
Dent disease is a rare X-linked renal proximal tubulopathy presenting with low-molecular-weight proteinuria (LMWP), hypercalciuria, and nephrocalcinosis, other signs of incomplete renal Fanconi syndrome, and renal failure. Early identification of patients who harbor disease-associated mutations is important for effective medical care and avoidance of unnecessary interventions. We report the case of an asymptomatic 9-year-old boy who presented with proteinuria in routine examination. Further investigation revealed the presence of nephrotic range proteinuria, mostly LMWP and mild hypercalciuria without nephrocalcinosis, or other features of tubular dysfunction. Renal function, growth, and bone mineral density were within regular limits. The male gender and the presence of LMWP and hypercalciuria even in the absence of other findings prompted us to genetic investigation for Dent disease. A novel splice site mutation (c.416–2A > G) of the chloride voltage-gated channel 5 (CLCN5) gene, responsible for Dent disease type 1 was identified. In silico analysis revealed that this mutation interferes with the mating of exons 4 and 5. Due to early molecular diagnosis, our patient did not undergo a renal biopsy, neither required aggressive pharmacological interventions. This case underscores the diversity and complexity of CLCN5 mutations and highlights the importance of early molecular testing in male patients with incomplete phenotype of Dent disease.
Keywords: Dent disease; CLCN5 mutation; proteinuria; hypercalciuria